Laser excitation of terahertz surface plasma wave over a hollow capillary plasma. (28th December 2015) - Singh, Rohtash; Tripathi, V. K.
Abstract: Two collinear laser pulses of finite spot size propagating through a capillary plasma, modeled as a hollow plasma cylinder, are shown to produce beat frequency terahertz (THz) surface plasmons at the inner surface. The evanescent laser fields in the plasma impart oscillatory velocity to electrons and exert a beat ponderomotive force on them. The static component of the ponderomotive force inhibits plasma from filling the vacuum region while the beat frequency component produces a nonlinear current ( ${\vec J^{{\;\rm NL}}}$ ) that drives the difference frequency THz surface plasma wave (SPW). Phase matching for the THz surface wave excitation is achieved when the group velocity of the lasers equals the phase velocity of the beat frequency SPW. At laser intensities of ~10 14 W/cm 2 at 10 μm wavelength, one may attain normalized surface wave amplitude ~ 0.03.